Africa as a phonological area - (:unkn) unknown (My University, 2008)
The central thesis of this chapter is that the African continent can be divided into six major zones, each of which is defined by a number of phonological properties that occur commonly within it but much less often outside it. It is organized around two main "core" sections, the first dealing with segmental phonological properties and the second with prosodic properties. Each begins with a brief overview and then examines a number of selected features in more detail. In our selection of features we have given priority to those that are well documented in a large number of languages, that appear in genetically distant (but not necessarily totally unrelated) languages in a contiguous area, that are broadly represented across smaller genetic units within this area, and that appear with much less frequency in languages outside the area, and outside Africa. The chapter concludes with a review of proposed diagnostics of the major zones.
Keywords: African Research